2015
DOI: 10.1016/j.jveb.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of different objects during a novel object test in stabled horses

Abstract: a b s t r a c tNovel object tests are often used to evaluate a horse's temperament by recording fear responses toward an unfamiliar object, but they might also be used as a part of welfare assessment. Various objects are used during these tests. This study aims to verify the use of different objects during a novel object test performed in the horse's stall. To this end, 54 horses and 4 objects (red-white striped cone [RWCONE]; a red-yellow plastic ball [BALL]; a black open umbrella [UMBR]; black-yellow striped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
3
10
0
1
Order By: Relevance
“…Like others, we found a greater reaction to an umbrella than to a ball (or ball-like stimulus such as a cone e.g. [34,35]). Although theoretically, this might simply relate to the umbrella being larger, for example, Bulens et al (2015) [35] suggested that the large size of an opened umbrella makes it di cult to ignore compared to the cone and plastic ball used in their test.…”
Section: Discussionsupporting
confidence: 86%
“…Like others, we found a greater reaction to an umbrella than to a ball (or ball-like stimulus such as a cone e.g. [34,35]). Although theoretically, this might simply relate to the umbrella being larger, for example, Bulens et al (2015) [35] suggested that the large size of an opened umbrella makes it di cult to ignore compared to the cone and plastic ball used in their test.…”
Section: Discussionsupporting
confidence: 86%
“…The results proved the absence of discrimination for the colour differences; the stallions behaved similarly, irrespective to the colour of the ball. This is similar to the results of other studies (Bulens et al, 2015;Christensen et al, 2008). Horses of both breeds were mostly vigilant and focused on the novel object in the first stage of the test, but after their interest decreased, in the same way as Gorecka et al (2007) observed.…”
Section: Abstract: Behavioural Indicators Novel Object Test Stallionssupporting
confidence: 91%
“…The way in which the horse reacts to novelty is crucial for safety of both horses and humans (Gorecka et al, 2007). Novel object tests are often used to test the horse's temperamental characteristics, to select the right horse for a specific rider and to assess welfare (Bulens et al, 2015). In our knowledge no such study was made until now in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…and the positive relationship between interest in novel objects and housing / social contact found byBulens et al (2015) further emphasizes the need to consider more appropriate housing and social access for domestic horses. The level of emotional responsiveness has been used as a means of assessing temperament in horses, with responses to novel objects being found to correlate well with other measures (reactivity testing:…”
mentioning
confidence: 99%